Safe drinking water and toilet facility in public places in India: What we need to do! - Paul, Swapan Kumar (J Family Med Prim Care, 2020)
There is abundant literature on domestic safe water supply and hygienic sanitation. Yet, there is a paucity of research studies on adequate supply of safe drinking water and toilet facilities in places of population movement and congregation in India. This study stresses on the importance of availability of safe water and sanitation facilities in all the places of human congregation and movement in India. 49 research studies were identified from 169 potentially relevant publications. Studies were selected: first, all protocols of water and toilet facilities among published literature were meticulously searched. Second, information sources on sanitation facilities in public life, viz., railways, roadways, waterways, market places and shopping complexes, schools, and other higher educational institutions, fairs and festivals, entertainment establishments, healthcare facilities, were explored from publications of various resources of different levels. Third, published reports from apex bodies of national and international importance like Indian Council of Medical Research, World Health Organization (WHO), UNICEF, USAID, etc. were given due weightage. Of late, the concept of cleanliness and making communities free from open defecation are in limelight as the Government of India has taken up Swachh Bharat Mission (SBM); even then, contextual gaps remain. This is the cause for concern as both safe water supply and basic sanitation are directly linked to health promotion of the community. Further, this research group have noted that due importance has not been integrated in the planning of SBM regarding availability of safe water and scientific sanitation facilities in all the places of human movement and congregation. Hence, there is more need for creating awareness among general population as well as stakeholders regarding this aspect of cleanliness. It is noted that despite considerable improvement in safe water and sanitation facilities in domestic life, there is considerable population left, who are still lacking access to these facilities in public space.